Lu-Hf geochronology on cm-sized garnets using microsampling: New constraints on garnet growth rates and duration of metamorphism during continental collision (Menderes Massif, Turkey) - Schmidt, A.; Pourteau, Amaury; Candan, O.; Oberhänsli, R. (2015)
© 2015 Elsevier B.V. This study shows Lu-Hf geochronology of zoned garnet crystals contained in mica schists from the southern Menderes Massif, Turkey. Selected samples are four 3-5 cm large garnet megacrysts of which several consecutive garnet shells have been sampled with a micro-saw and analyzed for dating. The results are used to extract growth rates of garnet, and also to improve the time constraint for Alpine-aged overprint of the Pan-African basement in the Menderes Massif.Lu-Hf ages of the sampled garnet shells are determined by two-point garnet-only isochrons using the garnets' Lu-depleted rim compositions. This yields a consistent decrease of age information from core to rim segments of individual garnet crystals and the calculated isochron ages propose a time frame of growth between 42.6. ±. 1.9 and 34.8. ±. 3.1 Ma. Major element profiles in the investigated garnets characterize zoning patterns indicative of prograde conditions: Rayleigh fractionated bell-shaped Mn and decreasing Fe/(Fe + Mg) are recorded by the garnets' core to rim compositions. Therefore the obtained Lu-Hf ages record timing of early prograde growth for the cores of the garnets. Two of the large garnet crystals also yield isochron ages of 58.83. ±. 0.69 and 50.16. ±. 0.84 Ma in their innermost cores, which appear to record an early nucleation event. This view, however, is not in concordance with the observed major element profiles of these garnets, and therefore is interpreted with caution. Termination of the garnet growth period is determined through the calculation of radial growth rates based on the size of the garnets and the Lu-Hf ages obtained for consecutive shells. Extrapolation of these rates potentially constrains the total duration for garnet growth terminating at 31. ±. 6 Ma. Comparison of the growth rates calculated for individual crystals shows a variety of slow and fast growing garnets, and similar results have been previously obtained with the Rb-Sr and Sm-Nd isotope systems.The new data provides a precise age determination for prograde Barrovian metamorphism in the southern Menderes Massif, which so far was placed between 63 and 27 Ma on the basis of mica Rb-Sr and Ar-Ar dating. This study provides new constraints crucial to the understanding of the tectonic evolution of southwest Anatolia and the Aegean realm, as it yields a shorter outline for Alpine aged continental collision.